Design of high gain and wideband circular patch antenna based on DGS for 28 GHz 5G applications - Md. Sohel Rana; Md. Nahid Hasan; Mohammad Faisal; Md Emran Khan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
In this study, a single band 28 GHz antenna with defected ground structure (DGS) has been proposed. The integration of a DGS is explored to exploit ground plane defects for achieving wideband operation. Through systematic design and optimization, our approach achieves remarkable bandwidth enhancement, expanding from 0.75 GHz to 5.78 GHz, covering frequencies from 26.43 GHz to 32.21 GHz, resulting in an impressive impedance bandwidth of 20.5%. Notably, the proposed methodology significantly improves the reflection coefficient, reducing it from -16 dB to -57 dB. Furthermore, the antenna demonstrates a gain of 5.123 dBi and an enhanced voltage standing wave ratio (VSWR) of 1.0056348. Comparative analysis against existing works underscores the superior performance of our antenna design, affirming its potential for various applications. This work presents a novel DGS featuring a circular microstrip patch antenna (MPA) with dimensions of 8×8×0.5 m³, utilizing Rogers RT5880LZ substrate (E=2) with a thickness of 0.5 mm.